Electrochemically Driven Giant Resistive Switching in Perovskite Nickelates Heterostructures - Wang, Le (2018)
The rich phase diagrams and peculiar physical properties of rare earth perovskite nickelates (RNiO3) have recently attracted much attention. Their electronic structures are highly sensitive to carrier density and bandwidth due to Mott physics. Here, the electrochemically driven giant resistive switching in Pt/RNiO3/Nb‐SrTiO3 heterostructures is reported. Systematic investigation confirms that oxygen vacancies migration modifies the interfacial barrier at the RNiO3/Nb‐SrTiO3 interface and causes the resistive switching behavior. An ON/OFF ratio of about 105 at room temperature is observed, which can be modulated by controlling the oxygen vacancies during sample fabrication or by varying the rare earth element in RNiO3. The findings provide an important step forward toward the development of multifunctional electronic devices based on perovskite nickelates.